3D Porous N‐Doped Graphene Frameworks Made of Interconnected Nanocages for Ultrahigh‐Rate and Long‐Life Li–O2 Batteries. (19th October 2015) - Zhao, Changtai; Yu, Chang; Liu, Shaohong; Yang, Juan; Fan, Xiaoming; Huang, Huawei; Qiu, Jieshan
Abstract : The inferior rate capability and poor cycle stability of the present Li–O2 batteries are still critical obstacles for practice applications. Configuring novel and integrated air electrode materials with unique structure and tunable chemical compositions is one of the efficient strategies to solve these bottleneck problems. Herein, a novel strategy for synthesis of 3D porous N‐doped graphene aerogels (NPGAs) with frameworks constructed by interconnected nanocages with the aid of polystyrene sphere@polydopamine is reported. The interconnected nanocages as the basic building unit of graphene sheets are assembled inside the skeletons of 3D graphene aerogels, leading to the 3D NPGA with well‐developed interconnected channels and the full exposure of electrochemically active sites. Benefiting from such an unique structure, the as‐made NPGA delivers a high specific capacity, an excellent rate capacity of 5978 mA h g −1 at 3.2 A g −1, and long cycle stability, especially at a large current density (54 cycles at 1 A g −1 ), indicative of boosted rate capability and cycle life as air electrodes for Li–O2 batteries. More importantly, based on the total mass of C+Li2 O2, a gravimetric energy density of 2400 W h kg −1 for the NPGA–O2 //Li cell is delivered at a power density of 1300 W kg −1 . Abstract : 3D porous N‐doped graphene frameworks constructed by interconnected nanocages are configured with the aid of polystyrene sphere@polydopamine. The interconnected nanocages as the basic building unit of graphene sheets are assembled inside skeletons of graphene aerogels, resulting in well‐developed interconnected channels and full exposure of heteroatom sites, thus help to boost the rate capability and cycle life for Li–O2 batteries.